Pengembangan Modul Reaksi Reduksi dan Oksidasi Berbasis Guided Discovery Learning untuk Kelas X SMA - Rahmatillah Wanti; Yerimadesi Yerimadesi (Universitas Negeri Padang, 2019)
This research aims to produce a guided discovery based module on redox reaction, also to determine its validity and practicality. This research used Research and Development type, which is a research that will develop and produce a certain product. This research used Plomp model which consists of three stages, preliminary research, prototyping stage, and assessment phase. The instrument used for this research is questionnaire, which consists of validity and practicality sheet. The product validated by two lecturers from Chemistry Department FMIPA UNP and two chemistry teachers from SMAN 12 Padang. The practicality test has been done by 2 chemistry teachers and 25 students of SMAN 12 Padang. The analysis result of validity sheet, teacher practicality and student practicality showed the average Kappa moment (k) respectively, 0.82, 0.87, and 0.81. The data obtained show that the module reduction and oxidation reactions based on guided discovery learning are valid and practical.